Redefining Islamic garden: comparative analysis of approaches, ideas and design framework - Asif, Nayeem; Utaberta, Nangkula; Othuman Mydin, M. A.; Mohd Yunus, Mohd. Yazid (Penerbit UTM Press, 2015)
The term Islamic garden has been defined in various ways considering different aspects and values. These definitions draw a broader perspective to Islamic garden, a key feature of Islamic civilization throughout the history. This paper aims to analyze these views and compare them in order to reach toward a holistic definition for Islamic garden- its origin, evolution, principles and essence. Also searching for a way to revitalize the original essence and application of Islamic gardens in the contemporary societies are discussed in a brief way.